Portrayal of Maslow’s Self-Actualization in Kafka’s ‘A Hunger Artist’ - Putri Rindu Kinasih (Universitas Bunda Mulia, 2020)
Because of his creativity, Kafka’s works have discussed and analyzed by the scholars for years. Interpretations of Kafka’s work has been done in various field of study, and among his writings, ‘A Hunger Artist’ isconsidered as the most transparent and clearest piece. However, the piece shows many bewildering complication of details. The artist’s obsession towards fasting has raised a number of questions; if he is into fasting then why he has to exhibit himself? This research aims to analyze the artist’s peculiar behavior by using Maslow’s concept of self-actualization. Maslow believed that in order to be able self-actualizing, a person must be brave enough to leave his comfort zone. This study shows that the artist fails in achieving Maslow’s concept of self-actualization as he stubbornly cling to the easiest thing he knows how to do, fast. Being able to fast more than forty days is not the expression of self-actualization because fasting is the comfort zone that he refused to let go.In addition, the artist’s obsession towards the spectator’s admirationhas prevent him from enjoying the exploration of his life and he lives in a constant depression. Ironically, the artist dies in hunger, an art that he totally masters.